POLA KOMUNIKASI ISLAM TERHADAP TRADISI HETERODOKS (Studi Kasus Tradisi Ruwatan) - Yanti, Fitri (Universitas Islam Negeri Raden Intan Lampung, 2013)
Javanese culture are not only provided color in government in Indonesia but also gives influence to religious practice. Java communities who are predominantly muslim can not leave their cultural traditions until now day, even though sometimes it goes against the Islamic worship (heterodox). Ruwatan is a worship that man saved from disruption and disaster that threatens their lives. Through ruwatan people feel protected by a large force that is believed to be the power of the savior, this phenomena continues until now. With add the Islamic shari’ah that does not prevent to implement ruwatan and morbidly eliminating the usual tradition at the usual tradition at the communicaties, and do not deviate from the Islamic aqeedah and morals in the Al-qur’an and Hadits of prophet Muhammad. Shirk and bid’ah directed towards monotheism and sunnah. The practice include read surah Yasin by congregation, read tayyibah and prayers to our prophet. Say a prayer (pleading to Allah swt) in order to avoid our family from distress and given the salvation of the world and the here after, held shadaqah/ charity which was served to the participants of the ceremony ruwatan